Presupuestos 2007-2012 y reducción del gasto público para obtener el crecimiento económico de España - Fernández, Ángel Fernández (REVISTA PROCESOS DE MERCADO, 2013)
The study observes the size of the Spanish State by analyzing the composition of the public spending policies in the Public Budget for the years 2007-2012. The government expenditure (central State, autonomous communities and local authorities) has not been reduced to the level required to achieve the control of the public debt. Furthermore, the fiscal adjustment must be done without tax increases because they are harmful for the dynamic efficiency of the economy. Secondly, the study explains the Production Structure of Capital from the perspective of the Austrian School of Economics and, including references and bibliography of previous studies, it shows how the tax increases are against the economic growth, because lower the private saving which is necessary in order to undertake investments and produce the goods of superior order that characterize the developed economies. Finally, the study explains the need to implement an Austerity Plan to reduce the public spending in Spain, in a serious way, by mean of: 1) cut the public budget in order to keep the public administrations in the medium and long term, 2) implement structural reforms to maintain balanced bud gets, 3) fa-cilitate the monitoring by the State Audits Agency, and 4) imple ment certain institutional barriers in the public Law in order to prevent the enlargement of the State by the interventionism of politicians that advocate public deficits and unlimited borrowing. Key words: Financial Crisis, Fiscal Policy, Public Finance (budget) deficit, So - vereign Debt, Public Administration, Economic Growth, Economic Policy. JEL Classification: G01, H30, H61, H62, H63, H83, O40, P16. Resumen: Este trabajo estudia el tamaño del Estado analizando la compo-sición de las políticas de gasto público en los Presupuestos Generales del Estado de los años 2007 a 2012. El gasto público no se ha reducido en las administraciones públicas (Estado central, autonomías y entidades locales) hasta el nivel requerido para lograr controlar el nivel de la deuda pública. Adicionalmente, el ajuste fiscal debe ser realizado sin subidas de impuestos que perjudican la eficiencia dinámica de la economía. En segundo lugar, el presente artículo explica la estructura productiva del capital según la Escuela Austriaca de Economía y razona, incluyendo refe-rencias y bibliografía de estudios previos, cómo las subidas de impuestos son perjudiciales para el crecimiento económico, porque se disminuye el ahorro privado previo que es necesario para acometer las inversiones y pro - ducir los bienes de órdenes superiores que caracterizan a las economías más desarrolladas. Finalmente, se explica cómo todavía existe una urgente necesidad de imple-mentar un Plan de Austeridad que reduzca el gasto público en España, de modo serio, basado en: 1) recortar y eliminar partidas presupuestarias para soste-ner las administraciones públicas en el medio y largo plazo, 2) implementar reformas estructurales que doten presupuestos equilibrados, 3) facilitar el control por la Intervención General del Estado, y 4) interponer barreras legislativas que eviten el aumento del tamaño del Estado con el intervencionismo de los políticos que propugnan déficit público y endeudamiento sin límites. Palabras clave: Crisis Financiera, Política fiscal, Déficit Público, Deuda So-berana, Administración Pública, Crecimiento Económico, Economía Política. Clasificación JEL: G01, H30, H61, H62, H63, H83, O40, P16.